Aplikasi Persebaran Peserta BPJS Kesehatan di Sumatera Utara Berbasis Pemetaan - Arie Rafika Dewi, Septiana Dewi Andriana, Eka Rahayu (Program Studi Sistem Informasi, 2017)
Health is the most crucial thing in the life of society, for that in every country must have a responsible institution in that case. Indonesian has an institution in charge of health. BPJS Kesehatan is a social insurance provider body established by the Indonesian government to give health insurance for the society. BPJS Kesehatan is a government-run social security agency that providing health insurance for the society. In accordance with vision of the BPJS Kesehatan that is Coverage Universe 2019, the entire population of Indonesian must have a national health insurance before January 1 2019. Therefore, it is necessary to mapping that can cover the subject, so that BPJS Kesehatan will be easier in prioritizing any regency or city in Indonesia (especially in North Sumatra) have given socialization first. These districts and cities would be informed of the benefits of health care and protection in meeting basic health needs organized by BPJS Kesehatan. Mapping has done using ArcView GIS.